Pathological changes in placentas of pregnant females with Gestational hypertension - Dhakal, Binod; Singh, VK; Narasimhan, Raghavan; Talwar, OP (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
Background: Hypertensive disorders complicating pregnancy are common and contribute greatly to maternal and fetal morbidity and mortality. The complications of hyper-tensive disorders in pregnancy have been attributed to abnormalities in the placenta. This study aims to observe the clinical, gross and microscopical (morphology) effects of pregnancy induced hypertension, preeclampsia and Eclampsia. Methods: It was a prospective study conducted in 30 placentas of hypertensive disorder of pregnancy and 20 placentas of normal pregnancy. The placentas with hypertensive disorders of pregnancy were compared with the placentas of normal pregnancy. Results: The mean age of mother at delivery was 28.1 years, 25.04 years and 25.04 years in pregnancy induced hypertension, preeclampsia and normal pregnancy respectively. The mean birth weight of new born babies, the mean placental weight and volume were found to be much lower than the control group. The risk for prematurity along with gross and histological abnormalities such as the presence of necrosis, villous hypermaturity, lymphohistiocytic villitis, avascular villi, perivillous fibrin deposits, hyalinization, stromal fibrosis, calcification and vessel wall thickening were observed significantly more often in the placentas of hypertensive mothers. Conclusion: There is a significant Gross and microscopic changes observed in placentas of hypertensive mothers than the normal mothers. Similarly placental weight and volume were found to be much lower.